In Silico Study of Antioxidant Compounds in Ipomoea aquatica Forsk as Acetylcholinesterase (AChE) Enzyme Inhibitor in Alzheimer’s Disease - Nugraha, Salma E.P; Rini Madyastuti Purwono (Indonesian Journal of Chemical Science, 2025)
Alzheimer’s Disease is a form of dementia characterized by a progressive decline in cognitive function, encompassing various aspects of intellectual abilities. Acetylcholinesterase (AChE) is an enzyme that degrades the neurotransmitter acetylcholine and plays an important role in regulating neurotransmission at synapses across the nervous system. Disruption of this cholinergic transmission significantly impacts the development of Alzheimer's disease. Compounds with AChE inhibitory activity are known to be promising drug candidates for treating this disease. In this study, an in-silico analysis was conducted on antioxidant compounds, specifically carotenoid compounds from Ipomoea aquatica Forsk, to determine whether these compounds could be potential drug candidates for Alzheimer's treatment using molecular docking methods. The 3D structure of the Acetylcholinesterase (AChE) receptor was obtained from the Protein Data Bank, while the structure of the carotenoid compounds was obtained from the PubChem database. The software used for the molecular docking simulation was AutoDock Vina, with additional supporting software such as AutoDockTools 1.5.6, PyMOL, and LigPlot. The analysis results showed that β-carotene is the best antioxidant, with binding energy and inhibition constant values of -10.2 kcal/mol and 20.06 μM, respectively, with hydrogen bonding occurring at the amino acid residue PHE 295.